PERSEPSI GURU TENTANG KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DI SEKOLAH MENENGAH PERTAMA NEGERI KECAMATAN KOTO TANGAH KOTA PADANG - Wenitra Syahda Utami (Universitas Negeri Padang, 2014)
The goal of this research are to see information about implementation of managerial skills headmaster school. The population is 302 teachers and the sample is 67 people that taken by stratified proportional random sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using by comparing the average scores. The result of this research are the perception of teacher about implementation of managerial skills headmaster school in SMP negeri Kecamatan Koto Tangah Kota Padang stay in good enough category. Kata kunci: Managerial Skills Headmaster School